Flood risk assessment data access and equity in Metro Vancouver. Issue 4 (2nd October 2022) - Gouett-Hanna, Chris; Oulahen, Greg; Henstra, Daniel; Thistlethwaite, Jason
Abstract: Flood risk is increasing in many urban regions in Canada. Flood risk is the product of interaction between a flood hazard, the exposure of built assets, and the vulnerability of people to flood impacts. Flood risk assessment seeks to quantify each of these factors for a geographic space to identify areas with greater risk, which can inform public- and private-sector decision making. This study conducts a flood risk assessment of Metro Vancouver in British Columbia using only government-provided open data. It finds that flood hazards and social vulnerability are uneven across the study area, and it reveals inequity in open data access and quality between municipalities. It concludes that more standardized or centralized provision of open data could better support flood risk analysis in Metro Vancouver, which could inform flood management and help to reduce local risk.